The Influence of Online Gaming Addiction on Depression in Adolescents - Boby Nurmagandi; Irfan Wabula; Risna Damayanti (Indonesian Journal of Global Health Research, 2025)
Nowadays, there is a rapid increase of online games. In fact, Indonesia ranks as the 3rd highest online game users in the world. It is teenagers who become one of the biggest users of online games. An excessive online game playing can have an impact on mental health problems, including online gaming addiction, clinical distress, and even depression. Objective: The purpose of this study was to determine whether there is an effect of online gaming addiction on depression problems in adolescent online game users. Method: The type of research used is a quantitative method with Cross Sectional approach. The sample in the study amounted to 297 high school adolescents in Majene district, West Sulawesi. Determination of the sample used purposive sampling based on the inclusion and exclusion criteria set. Results: The results of this study showed that most adolescents experienced moderate online game addiction, namely 191 adolescents (64.3%) and most adolescents experienced moderate depression as many as 79 adolescents (26.6%). There was a significant relationship between online gaming addiction in adolescents with depression problems experienced by adolescents with p value < 0.05. Conclusions: Online game addiction in adolescents had a 3 times greater influence on depression problems in adolescents. Joint action was needed from schools, health institutions and families to overcome and to prevent the problem of online game addiction and depression in adolescents.